A Novel Approach for the Processing of Advanced Polymer Derived Ceramics with Carbon Nanotubes with the Help of Pores1. Issue 3 (4th September 2013) - Mantzel, Niko; Rannabauer, Stefan; Bucharsky, Ethel C.; Schell, Karl G.; Hoffmann, Michael J.; Scheffler, Michael; Stephani, Günter; Scheffler, Michael
<x xml:space="preserve">Abstract</x> In a novel approach, a nickel‐doped carbon rich preceramic polymer is converted into a carbon nanotubes (CNT) bearing polymer derived ceramic (PDC). Milling and field‐assisted sintering demonstrate that the CNTs remained stable during processing, and the CNTs are found to be embedded in the PDC matrix. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>